GRAVIDARY HOMEOSTASIS IN PREGNANT WOMEN WITH UNDERWEIGHT - Елена Владимировна Рудаева; Галина Александровна Ушакова (The Publishing House Medicine and Enlightenment, 2017)
In recent years considerable success has been achieved in reducing obstetric and perinatal complications in various pathological conditions during pregnancy and childbirth. However, many aspects of obstetrics, theoretical and practical, remain unresolved. A promising direction are the new methodological approaches to clinical research methods of physiological and complicated pregnancy. One of such directions is the study of the gravidary homeostasis. The study of the gravidary homeostasis in pregnant women with underweight opens up fundamentally new ways to reduce the obstetric and perinatal complications. The aim - was to study the gravidar homeostasis in pregnant women with a body weight deficit. Materials and methods. A survey of 50 pregnant women with a deficit of body weight and their fetuses (the main group). The comparison group consisted of 50 pregnant women with normal body weight and their fruits. Neurovegetative regulation of the heart rhythm of the mother and fetus was studied by the method of spectral and mathematical analysis of the variability of the heart rhythm. Results. When registering the initial profile of the heart rhythm, only 16 % of women with body weight deficit of the cardiothoracic wave SPM were within the conditional norm (92 %; p < 0,001). An increase in the SPM waves of cardiac rhythm (hyperadaptive state) due to VLF and LF-components of the spectrum was recorded in 48 % of women (6 %; p < 0,001). In 36 % of pregnant SPM waves, cardiac rhythm was characterized by a general depression of the spectrum (2 %; p < 0,001). In carrying out the functional loading test (hyperventilation), hyperadaptive stress responses (10 %; p < 0,001) prevailed in 50 % of cases. During the recovery period, 60 % of pregnant women showed a decrease in the adaptive mechanisms of the mother's body (12 %; p < 0,001). The indices of the cardiac rhythm wave fetal wave in a mother with a body weight deficit in 60 % were characterized as a hyperadaptive state (8 %; p < 0,001). Conclusion. Investigation of the gravidar homeostasis in pregnant women with a deficiency of body weight opens new possibilities for reducing obstetric and perinatal complications. The mother's homeostasis with a deficiency in body weight was characterized by a pronounced activation of the sympathoadrenal system, the voltage of the compensatory mechanisms. The fetus experienced a gradual decrease in the effectiveness of its own regulatory influences on the part of the neurovegetative system on the heart rhythm.